Tata Kelola Gereja: Sebuah Tinjauan Sistematis Literatur - Wisnu Haryo Pramudya; Julianto Agung Saputro; Atika Jauharia Hatta (JURNAL ILMIAH GEMA PERENCANA, 2025)
This study is a qualitative research that aims to systematically examine the scholarly literature on church governance over the past three decades, with a focus on identifying key concepts, practices, challenges, and opportunities in church management from theological, organizational, and cultural perspectives. The primary issue addressed is the absence of a conceptual consensus and clear indicators of ecclesiastical governance success, as well as the lack of studies integrating systematic approaches across traditions and disciplines. This research addresses a gap in the literature by providing a comprehensive and systematic review of the evolution and practices of church governance. Utilizing the Systematic Literature Review (SLR) method based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines and the Scopus database, 20 selected scholarly articles were analyzed thematically and bibliometrically. The analysis reveals that church governance has evolved from hierarchical and centralized models toward more participatory and contextual patterns, influenced by social, political, and theological dynamics. The findings also highlight the importance of integrating Gospel values, transparency, congregational participation, and sensitivity to local contexts in designing governance models that are relevant in the modern era. Nonetheless, normative, structural, and cultural challenges remain significant obstacles to effective and inclusive church management practices.